Calculation Model for the Selection of Physical Dimensions of a New Type of Heating Curing Building. Issue 1 (1st February 2022) - Yu, N; Shen, Z; Wu, J S; Kong, X R
Abstract: The spatial pattern of the new type of heating curing building directly affects the energy consumption of the PC component and the passive utilisation efficiency of solar energy. Based on the thermal design theory and building energy consumption simulation analysis method, this study constructed the heating-curing energy consumption model and determined the evaluation index of building space shape parameters. Based on the energy consumption model and Energy Plus simulation software, the calculation case—the best spatial shape characteristic parameters of the new-type heating and curing building in the Shijiazhuang area was given. Compared with the traditional steam warming curing, the carbon emission per unit building area was reduced by 33.4% each year, and the carbon emission of one ton of PC component was reduced by 0.97t.